Revolutionary terror campaigns in Addis Ababa, 1976-1978 - Wiebel, J (2014)
Between 1976 and 1978, urban Ethiopia became a site of collective violence. Rival campaigns of revolutionary terror were fought out, most notably in the capital city of Addis Ababa. Opposition forces launched targeted assassinations against the military regime and its collaborators, prompting the latter to widen early campaigns of repression into one of the most brutal reigns of state terror in modern Africa. Tens of thousands of Ethiopians, most of them young and many educated, lost their lives. Thousands more were systematically tortured or otherwise abused. Many escaped to the countryside or fled abroad, invigorating rural insurgencies and generating the country's first permanent diaspora. The Terror effected deep changes in Ethiopian state and society, as well as in relations between them. This thesis analyses the social and political history of this revolutionary violence. It brings materials familiar to scholars of modern Ethiopia together with new sources, from oral interviews to international archives. On the basis of these sources, the dynamics and aftereffects of the Ethiopian Terror are examined. Urban Ethiopia's revolutionary violence is shown to have been jointly produced by supralocal decision makers and by local actors, shaped by centrally imposed structures as much as by locally moulded operational cultures. Geo-political alliances in the context of the global Cold War had profound effects on the mode of violence on the ground. Underpinning this violence were evolving social processes and narratives that legitimised terror campaigns and depersonalised opponents. Unveiling these dynamics of violence, this thesis traces the changes in the Terror’s forms and agents. The mode of state-instigated violence shifted significantly: it transitioned from unsystematic repression before February 1977 to a phase of decentralisation that lasted until July 1977, during which the means of state violence were devolved to local actors. It culminated in a centrally coordinated campaign of terror in late 1977 and early '78, which inscribed institutional structures and practices of collective violence into the state bureaucracy. Opposition violence, meanwhile, moved into the opposite direction, becoming increasingly localised and less subject to centralised control. Having surveyed these defining dynamics of revolutionary violence, the thesis traces their subsequent trajectories, highlighting the enduring repercussions of the Terror's legacies and of its contested memorialisation process for Ethiopian politics and society.